2019
DOI: 10.1016/j.neubiorev.2019.09.036
|View full text |Cite
|
Sign up to set email alerts
|

How does cannabidiol (CBD) influence the acute effects of delta-9-tetrahydrocannabinol (THC) in humans? A systematic review

Abstract: The recent liberalisation of cannabis regulation has increased public and scientific debate about its potential benefits and risks. A key focus has been the extent to which cannabidiol (CBD) might influence the acute effects of delta-9-tetrahydrocannabinol (THC), but this has never been reviewed systematically. In this systematic review of how CBD influences the acute effects of THC we identified 16 studies involving 466 participants. Ten studies were judged at low risk of bias. The findings were mixed, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(130 citation statements)
references
References 132 publications
2
112
0
6
Order By: Relevance
“…Similarly, a lower age of onset of cannabis use [17,19,21] and the use of more potent types of cannabis, with higher THC and lower cannabidiol (CBD) concentrations [22,28], have been shown to further increase the risk of psychosis. CBD is a non-intoxicating cannabinoid compound that may attenuate some of the negative effects associated with cannabis use [29][30][31]. The genetic profile of cannabis users has also been implicated as a moderator of the association between cannabis use and the development of psychosis [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a lower age of onset of cannabis use [17,19,21] and the use of more potent types of cannabis, with higher THC and lower cannabidiol (CBD) concentrations [22,28], have been shown to further increase the risk of psychosis. CBD is a non-intoxicating cannabinoid compound that may attenuate some of the negative effects associated with cannabis use [29][30][31]. The genetic profile of cannabis users has also been implicated as a moderator of the association between cannabis use and the development of psychosis [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…16 However, the quality of CBD products has been found to be inconsistent; hence the United States Food and Drug Administration (FDA) has tested the chemical content of cannabinoid compounds in some products, and, not surprisingly, they found many products did not contain the levels of CBD claimed in their labeling. 17 A recent systematic review suggested that CBD may interact with some acute effects of THC. However, the findings were mixed (as CBD did not consistently influence the effects of THC across all studies and outcomes), although CBD was found to reduce the effects of THC in several of the reviewed studies.…”
Section: What Type Of Products Might Be Available?mentioning
confidence: 99%
“…However, it is noteworthy that these products do not always meet the quality standards acceptable by the pharmaceutical industry. 17 Therefore, in our view the MCI should aim to develop products (oral or parenteral) with standardized content, a characterized manufacturing process, and a defined shelf-life. These products should also be supported by valid clinical studies proving their safety and efficacy.…”
Section: What Type Of Products Might Be Available?mentioning
confidence: 99%
“…Dans une Ă©tude amĂ©ricaine rĂ©cente, trois fumeurs de cannabis sur 10 remplissent les critĂšres d'un trouble liĂ© Ă  l'usage de cannabis selon les critĂšres du DSM-IV et, la prĂ©valence du trouble liĂ© Ă  l'usage de cannabis Ă©valuĂ© sur l'annĂ©e derniĂšre a doublĂ© chez les adultes amĂ©ricains depuis 2001 [46]. À l'inverse, le cannabidiol pourrait avoir des propriĂ©tĂ©s « protectrices » [47] mais les rĂ©sultats Ă  ce jour restent controversĂ©s [48,49]. En particulier, un essai a suggĂ©rĂ© l'intĂ©rĂȘt du CBD pour attĂ©nuer les troubles psychotiques [50] mais une autre Ă©tude a obtenu des rĂ©sultats nĂ©gatifs [51].…”
Section: Complications Psychiatriquesunclassified